Water characteristic curves of geosynthetic clay liners hydrated by a saline solution. Issue 2 (19th April 2021) - Yu, B.; El-Zein, A.
Abstract : Geosynthetic clay liners (GCLs) are used in saline environments but little is known about their soil water characteristic curve (SWCC) when exposed to saline solutions. This paper presents an investigation of the SWCC of three different types of GCLs, which were hydrated with deionised (DI) water and a 0.325 mol/l sodium (Na + ) synthetic brine pond solution (NaCl, NaHCO3 and Na2 CO3 ). One of the GCLs was made of bentonite modified with polyacrylamide polymer. Higher air-entry values and steeper slopes of SWCCs between the two inflection points were observed in samples hydrated with synthetic brine. Polymer addition increased the water retention of the GCL under both DI and brine hydration. Brine hydration was found to reduce the total mass of liquid absorbed by the bentonite, compared to DI water. Total suction under brine was found to be different from the sum of total suction under DI and osmotic suctions of the brine solution, which may be due to the loss of osmotic swelling and crystallisation of salt in air-filled pores. Compared to the more frequently used Van-Genuchten and Fredlund-Xing models, the three-zone linear Pham-Fredlund model provided better SWCC fit for brine-hydrated GCLs.